1993
DOI: 10.1021/ie00023a057
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of mercury extraction using oleic acid

Abstract: In the absence of halide ion, Hg2+ is the predominant species in water and can be effectively extracted using oleic acid. The organic phase complex that is formed is HgRi2(RH). The presence of polar modifiers in the organic phase facilitates the formation of a complex dimer, [HgR2'2(RH)12. Kinetics of the extraction reaction have been studied as a function of pH, Hg2+ concentration, oleic acid concentration, and mixing rate in a stirred cell reactor. Extraction kinetics are first order in mercury concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…boundary conditions: Transport of mercury to the surface of the drop is controlled by mass transfer (eq 4), consistent with the results of the kinetic study which revealed that the mercury-oleic acid reaction is instantaneous (Larson and Wiencek, 1993). Consequently, at the interface, mercury in the aqueous phase is assumed to be in equilibrium with the mercury-oleic acid complex in the emulsion phase (eq 7).…”
Section: Model Formulation For Extraction Of Mercury With a Microemul...supporting
confidence: 81%
See 2 more Smart Citations
“…boundary conditions: Transport of mercury to the surface of the drop is controlled by mass transfer (eq 4), consistent with the results of the kinetic study which revealed that the mercury-oleic acid reaction is instantaneous (Larson and Wiencek, 1993). Consequently, at the interface, mercury in the aqueous phase is assumed to be in equilibrium with the mercury-oleic acid complex in the emulsion phase (eq 7).…”
Section: Model Formulation For Extraction Of Mercury With a Microemul...supporting
confidence: 81%
“…Equilibration time was 12 h. The internal-phase content was measured to be 15 wt % 6 N H2SO4 on a Mettler Model DL18 Karl Fischer titrator. A volume of 0.5 X 10~3 m3 of emulsion was dispersed into 5 X m3 of an aqueous solution containing 0.0025 kmol/m3 (511 ppm) mercury in a stirred contactor described in our earlier work (Larson and Wiencek, 1993). The agitation speed was 350 rpm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the mass-transfer behaviors within both films of liquid and SC CO 2 closely approach the linear driving force model (LDF model) of film theory, which assumes the concentration profile within the film is linear. In fact, the LDF model of film theory has been used to estimate the mass-transfer rate across the liquid film for studies of mercury extraction in a stirred tank under atmosphere [27,28]. In order to estimate the mass-transfer rate of the in situ chelation-SFE process, a simplified LDF model is proposed here.…”
Section: Kinetic Model For Estimating Mass-transfer Coefficientmentioning
confidence: 99%
“…In recent publications from our laboratory, we have demonstrated the advantages of using emulsion liquid membranes (ELMs) to extract heavy metals like mercury, copper, nickel, and zinc from aqueous waste streams (1)(2)(3). ELMs, first invented by Li (4), are made by forming an emulsion between two immiscible phases.…”
Section: Introductionmentioning
confidence: 99%